Philosophy in turbulent times Canguilhem, Sartre, Foucault, Althusser, Deleuze, Derrida - Roudinesco, Elisabeth (Columbia University Press, 2010)
For Elisabeth Roudinesco, a historian of psychoanalysis and one of France's leading intellectuals, Canguilhem, Sartre, Foucault, Althusser, Deleuze, and Derrida belong to a ""great generation"" of French philosophers. Innovative and troubled, these thinkers accomplished remarkable work and lived incredible lives, and though their cultural horizon was dominated by Marxism and psychoanalysis, they were by no means strict adherents to Marxist and Freudian doctrines. Having known many of these intellectuals personally, Roudinesco merges an account of their thought and experiences with her
Keywords: Philosophy : France : History : 20th century; Philosophy, French : 20th century